Respuesta :

Answer:

(2, [tex]\frac{13}{3}[/tex] )

Step-by-step explanation:

Given the 2 equations

2x + 3y = 17 → (1)

3y = 15 - x → (2)

Substitute 3y = 15 - x into (1)

2x + 15 - x = 17, that is

x + 15 = 17 ( subtract 15 from both sides )

x = 2

Substitute x = 2 into either of the 2 equations for corresponding value of y

Substituting in (1)

2(2) + 3y = 17

4 + 3y = 17 ( subtract 4 from both sides )

3y = 13 ( divide both sides by 3 )

y = [tex]\frac{13}{3}[/tex]

Solution is (2, [tex]\frac{13}{3}[/tex] )

Rearranging...

3y + x = 15

3y + 2x = 17

Using elimination method

2x - x = -15 + 17

X = 2

From equation.... 2

3y + 2 = 15

3y = 15 - 2

3y = 13

Y = 13/3

::x = 2 while y = 13/3

Ver imagen opeyemidaniel2004
ACCESS MORE